2019
DOI: 10.3390/ma12182934
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cr, W, and Mo on the High Temperature Oxidation of Ni-Based Superalloys

Abstract: The oxidation behavior of Ni–9.5Co–(8~12)Cr–(2.5~5.5)Mo–(4~8)W–3Al–5Ti–3Ta–0.1C–0.01B alloys was investigated at 850 °C and 1000 °C The mass change, the phase of oxides, and the cross-sectional structure of specimens were analyzed after cyclic oxidation tests. The oxide scale was composed mainly of Cr2O3 and NiCr2O4, but NiO, TiO2, and CrTaO4 were also found. Al2O3 was formed beneath the Cr oxide layer. The Cr oxide layer and internal Al oxide acted as barriers to oxidation at 850 °C, while Al oxide was predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Further research may identify other materials suitable for applications with molten sorbents. One promising avenue is refractory metal alloys with nickel, for example, a nickel–molybdenum or nickel–tungsten alloy . Refractory metals are highly resistant to corrosive attack under extreme conditions. , The added expense of more exotic alloys may be justified by reduced rates of corrosive and chemical degradation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Further research may identify other materials suitable for applications with molten sorbents. One promising avenue is refractory metal alloys with nickel, for example, a nickel–molybdenum or nickel–tungsten alloy . Refractory metals are highly resistant to corrosive attack under extreme conditions. , The added expense of more exotic alloys may be justified by reduced rates of corrosive and chemical degradation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…These reactions also occur for Ni and Ti. Park et al [30] also reported the presence of TiO 2 after hot corrosion of nickel-based superalloys. The Cr 2 O 3 phase is corrosion resistant, in contrast to TiO 2 and NiCr 2 O 4 [31].…”
Section: Characterization Methodsmentioning
confidence: 94%
“…49,50,55 Even more prominent is their deleterious effect on oxidation and corrosion resistance. In some studies, Mo and W were shown to increase oxidation rate, leading to a less protective scale, 47,64 whereas in others, Mo was reported to decrease the oxidation rate. 64,65 In 1976, Peters et al 66 observed substantially accelerated degradation at 900°C and the formation of a Mo-rich oxide for both salted and unsalted samples of ternary Ni-Cr-Mo alloys with high Mo contents.…”
Section: Spotlight: Role Of W and Momentioning
confidence: 99%